PHARMACOLOGICAL STUDIES: ANTIBACTERIAL, ANTIOXIDANT, AND ANTI-INFLAMMATORY EFFICACY OF CASUARINA EQUISETIFOLIA ROOT EXTRACTS - Vtk, Saranya; S, Uma Gowrie (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current study was aimed to investigate the potential phytoconstituents from Casuarina equisetifolia root extract. Qualitative, quantitative and gas chromatography–mass spectrometry (GC-MS) analysis of C. equisetifolia using various solvents of root extract was also carried out to characterize the presence of various bioactive compounds in the root. The research work was also targeted to reveal the antibacterial, antioxidant, and anti-inflammatory potential of the root extract of C. equisetifolia. Methods: Root samples of C. equisetifolia were collected from Nimilenchery village, Pondicherry Union territory. The qualitative screening of the root extracts was carried out to check the presence of various phytoconstituents which was then followed by the quantitative analysis of phenols, flavonoids, and tannins. Further, the phytochemicals in the root extract were evaluated using GC-MS studies. In vitro antibacterial activity was performed by the agar well diffusion method using aqueous and organic solvent-based root extract against four different bacterial pathogens. In vitro antioxidant assay of different solvent extracts was elucidated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, hydrogen peroxide radical scavenging assay, and reducing power assay. Anti-inflammatory potential was also studied using protein denaturation of albumin. Results: The qualitative phytochemical screening revealed the presence of various phytoconstituents which is of greater biological importance. Gallic acid equivalent (GAE) phenolic compound content (68.64±0.25 mg GAE/g of extract), quercetin equivalent flavonoid content (29.09±0.14 mg of QUE/g of extract), tannic acid equivalent (TAE) tannin content (51±0.42 mg TAE/g of extract), and terpenoid content (5.2%) were found to be significant in the methanol root extract of C. equisetifolia when compared with other solvents. GC-MS analysis revealed different peaks indicating the presence of different secondary metabolites. Prominent antibacterial activity was observed in methanol extract of root, with maximum zone of inhibition exhibited against Proteus vulgaris (23.45±0.28 mm). The methanol root extract was most effective with half maximal inhibitory concentration (IC50) 52.74±0.65 μg/ml for DPPH and 64.94±0.24 μg/ml for hydrogen peroxide scavenging activity. Maximum absorbance was observed by 80 μg/ml (IC50 51.79±0.26 μg/ml) of methanol root extract with respect to reducing power assay. In vitro anti-inflammatory activity had maximum inhibition of 84.6±0.26 with IC50 value of 33.6±0.23 μg/ml at 80 μg/ml. Conclusion: From this study, it is revealed that the species of C. equisetifolia is a source of potential phytoconstituents exhibiting significantly various biological activities leading to the development of novel drug.